Flexible Spacecraft Dynamics, Control and Guidance Technologies by Giovanni Campolo - Mazzini, Leonardo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book is an up-to-date compendium on spacecraft attitude and orbit control (AOC) that offers a systematic and complete treatment of the subject with the aim of imparting the theoretical and practical knowledge that is required by designers, engineers, and researchers. After an introduction on the kinematics of the flexible and agile space vehicles, the modern architecture and functions of an AOC system are described and the main AOC modes reviewed with possible design solutions and examples. The dynamics of the flexible body in space are then considered using an original Lagrangian approach suitable for the control applications of large space flexible structures. Subsequent chapters address optimal control theory, attitude control methods, and orbit control applications, including the optimal orbital transfer with finite and infinite thrust. The theory is integrated with a description of current propulsion systems, with the focus especially on the new electric propulsion systems and state of the art sensors and actuators.
Introduction -- The Kinematic of the flexible satellite -- The Satellite Attitude Control System -- The Dynamic of the flexible body -- The Dynamic in the Gravitational Field -- The Optimal Control Theory -- Attitude Control Methods -- Orbital Dynamic and Control -- Spacecraft Propulsion -- Sensors and Actuators technologies -- Complements to Body Kinematic -- Elements of Estimation Theory -- Basics of Lagrangian Equations -- The J2 perturbation solution -- Complements to Optimal Orbital Transfer -- Elements of Plasma physics.
Keywords: Aerospace engineering; Astronautics; Control engineering; Solar system; Aerospace Technology and Astronautics; Control and Systems Theory; Space Physics